Immobilized liquid metal nanoparticles with improved stability and photothermal performance for combinational therapy of tumor. (July 2019) - Hu, Jing-Jing; Liu, Miao-Deng; Chen, Ying; Gao, Fan; Peng, Si-Yuan; Xie, Bo-Ru; Li, Chu-Xin; Zeng, Xuan; Zhang, Xian-Zheng
Abstract: Various negative effects accompanying with the instability of bare liquid metal (LM) nanoparticles, including undesirable spontaneous coalescence, continuous photothermal performance deterioration and difficult multi-step functionalization, severely hinder its applications in biomedical area. In this study, we proposed a new concept of immobilized liquid metal nanoparticles based on a surface mesoporous silica coating strategy (LM@MSN). Strikingly, it was found that unsteady and vulnerable LM nanoparticles after immobilization exhibited enhanced stabilization and sustainable photothermal performance even with a long and repeated light irradiation in acidic environments. Moreover, integrating the properties of easy surface functionalization and high drug loading efficiency from silica shell, immobilized LM nanoparticle was further used for photothermal involved combinational therapy. The classical anticancer drug doxorubicin (DOX) was encapsulated in pores of silica shell and the hyaluronic acid (HA) was decorated on LM@MSN to construct LM@MSN/DOX@HA for tumor targeted combination therapy. Both in vitro and in vivo studies proved that LM@MSN/DOX@HA could significantly inhibit solid tumor growth under near infrared (NIR) irradiation by synergistic photothermal/chemotherapy. Graphical abstract: Image 1